A stable pillared metal–organic framework constructed by H4TCPP ligand as luminescent sensor for selective detection of TNP and Fe3+ ions. (22nd October 2019) - Ye, Yu; Sun, Libo; Zhang, Chenghui; Du, Jianfeng; Liu, Yuchuan; Song, Xiaowei; Liang, Zhiqiang
Abstract: A novel luminescent metal–organic framework (Zn‐TCPP/BPY ) with pillared structure based on 2, 3, 5, 6‐tetrakis(4‐carboxyphenyl)pyrazine (H4 TCPP) and 4, 4′‐bipyridine (BPY) has been designed and synthesized through a solvothermal reaction. The [Zn2 (COO)4 ] paddlewheel units are linked by TCPP 4− ligands to form two‐dimensional layers and further connected by BPY ligands as pillars to construct the twofold interpenetrating three‐dimensional framework. Interestingly, Zn‐TCPP/BPY possesses outstanding stability in organic solvents and water as well as maintains its structural rigidity in aqueous solutions of different pH values (3–12). After activation, Zn‐TCPP/BPY possesses permanent porosity with Brunauer–Emmett–Teller surface area of 630 m 2 g –1 . Remarkably, Zn‐TCPP/BPY displays excellent fluorescent property in virtue of the aggregation‐induced emission effect of the H4 TCPP ligand, which can be highly active and quenched by small amounts of 2, 4, 6‐trinitrophenol (TNP) and Fe 3+ ions. Furthermore, the detection effect of Zn‐TCPP/BPY remains basically the same even after five cycles. The excellent stability, high sensitivity, and recyclability of Zn‐TCPP/BPY make it an outstanding chemical sensor for detecting TNP and Fe 3+ ions. Abstract : A novel luminescent metal–organic framework with pillared structure has been constructed using 2, 3, 5, 6‐tetrakis(4‐carboxyphenyl)pyrazine (H4 TCPP) and 4, 4′‐bipyridyl ligands. It exhibits excellent physical and chemical stability, and luminescent sensing ability for 2, 4, 6‐trinitrophenol and Fe 3+ ions.